FOREIGN LANGUAGE EDUCATION OF KAZAKHSTAN: CURRENT TRENDS AND FUTURE PERSPECTIVES - Gerfanova, Elmira (PEOPLE: International Journal of Social Sciences, 2018)
The paper aims at analyzing the paradigms which influenced the development of Kazakhstan foreign language education, considers its trends and discusses the perspectives of its future development.The analysis of modernization processes in the national foreign language education reveals the following changes: reconsideration of the language policy which aims at developing trilingualism, i.e. the knowledge of Kazakh, Russian, and English has acquired much significance in Kazakhstani society; elaboration of the Concept of foreign language education of Kazakhstan which is a distinct theoretical and methodological framework defining the main ways and strategies of its development; establishment of educational organizations offering advanced learning of foreign languages; transition from traditional to new forms of education, such as MA and PhD; introduction of new specialties within BA, MA and PhD programs.